An Analysis of Slang Words in @Agnezmo's Posts On Instagram - Kesek, Philia Shallom; Kumayas, Tirza A; Rorimpandey, Rinny S (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This research aimsed to describe the form of slang and the meaning of the use of slang in Agnez Mo's posts on her Instagram account. The data source used in this research was in the form of sentences written in isntagram captions that show the form of slang and the meaning of the use of slang contained in Agnez Mo's account. The data collection technique used in this research is the free listening method followed by the note-taking technique. The data analysis used in this research is descriptive qualitative analysis that describes the form of slang and the meaning of the use of slang in Agnez Mo's posts. Using the theory of Keith Allah and Kate Burridge (2006), the result shows that there are 55 types of slang consisting of 1 Fresh and Creative, 13 Flippant, 10 Imitative, 6 Acronym, and 25 Clipping. Furthermore, it shows that slang is not just a language style, but also reflects social and cultural changes in the ever-evolving online communication, slang has become a part of everyday conversation to convey messages easily and casually.